Process Monitoring of CO2 Absorption in Diethanolamine Using Fourier Transform Infrared Spectroscopy (FTIR) - Norhashima, Mokhtar (2013)
The research is about the process monitoring of carbon dioxide (CO2) absorption in alkanolamine aqueous solution, Diethanolamine (DEA) by Fourier Transform Infrared Spectroscopy (FTIR). The CO2 gas level in the atmosphere is rising fast because of the human activities and industry process. It is important to capture CO2 gas from the flue gas to reduce the emission of gasses in atmosphere. Today, absorption of CO2 by various alkanolamine solutions is the dominant industrial process for solving the increasing of greenhouse gas emission. In this study, DEA is use as an absorbent in absorption of CO2. The first objective of the study is to obtain the FTIR spectrum of CO2-DEA system at different DEA concentration and CO2 flow rate. The concentrations of DEA are 2M, 4M and 6M. The CO2 flow rate is 100 and 200 ml/min. The experiment was performed at the constant stirrer speed, 120rpm. The second objective of the study is to synthesize FTIR spectrum to characterize the system using Principal Component Analysis (PCA). The experiment were be conducted by taking the sample for every 1h, 2h, 3h, 4h, 5h, 6h and 7h after CO2 addition in DEA solution. The samples were analyzed using FTIR. As the conclusion, FTIR spectra for CO2-DEA system are successfully obtained. FTIR are feasible to be used to monitor the absorption process of CO2 in different DEA concentration and CO2 flowrate because it gives a fast analysis and reliable measurement. The multivariate technique of Principal Component Analysis (PCA) can be applied to characterize the absorption behavior by resulting the spectrum obtained from the experiment. As the recommendation, the more analysis should be done to have better data in making comparison of each system. Besides that, the other variable also can be observed like temperature and pressure. The other amine also can be used as an absorbent like AMP and blending of MDEA with DEA.